2015
DOI: 10.5414/cn107945
|View full text |Cite
|
Sign up to set email alerts
|

Remission of C3 glomerulopathy with rituximab as only immunosuppressive therapy

Abstract: C3 glomerulopathy (C3GP) is a membranoproliferative glomerulonephritis without immunoglobulin deposits. Activation of the alternative pathway of the complement system is central in its pathogenesis. The presence of a C3 nephritic factor (C3Nef), or deficient factor H or I is associated with C3 GP. The treatment is not codified. Here we describe a case of a Caucasian male with a dense deposit disease (a form of C3GP) revealed by nephritic syndrome. C3Nef was present. We treated him with rituximab as the sole im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Genetic and serologic tests were performed on only one-third of the patients and determinations of C3NeF or other autoantibodies were not systematically collected or repeated along clinical course to evaluate the effect of immunosuppressive therapies. Other therapies that have been reported as useful in some C3GN patients, such as rituximab, 34 were not used in our patients. On the other hand, the major strengths of the study were the large number of included patients, the regular follow-up of all patients that allowed us to determine renal outcomes, the rigorous collection of clinical, biochemical, and histopathological data and the careful recording of all treatments and related side effects.…”
Section: Discussionmentioning
confidence: 87%
“…Genetic and serologic tests were performed on only one-third of the patients and determinations of C3NeF or other autoantibodies were not systematically collected or repeated along clinical course to evaluate the effect of immunosuppressive therapies. Other therapies that have been reported as useful in some C3GN patients, such as rituximab, 34 were not used in our patients. On the other hand, the major strengths of the study were the large number of included patients, the regular follow-up of all patients that allowed us to determine renal outcomes, the rigorous collection of clinical, biochemical, and histopathological data and the careful recording of all treatments and related side effects.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to nonspecific nephroprotective drugs such as renin-angiotensin system blockers, several observations suggest some efficacy of immunosuppressive therapies, including eculizumab, a monoclonal anti-C5 antibody targeting the final step of complement pathway, and agents targeting T and/or B cells with a potential effect on glomerular inflammation and production of auto-antibodies activating complement AP. [24][25][26][27] In a recent study, it has been suggested that mycophenolate mofetil may improve renal survival in C3G.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few case reports published on the use of B-cell depleting therapy to decrease production of C3Nef and subsequently to reduce proteinuria and stabilize or even improve renal function (Table 2). In one report a 34-year-old patient with DDD was treated solely with rituximab [40]. Low C3 and normal C4 indicated an activation of the alternative complement pathway, and C3Nef was found to be positive.…”
Section: Rituximab In C3gn and Dddmentioning
confidence: 99%